2020
DOI: 10.1007/s12182-019-00415-y
|View full text |Cite
|
Sign up to set email alerts
|

3D modeling of deepwater turbidite lobes: a review of the research status and progress

Abstract: Deepwater turbidite lobe reservoirs have massive hydrocarbon potential and represent one of the most promising exploration targets for hydrocarbon industry. Key elements of turbidite lobes internal heterogeneity include the architectural hierarchy and complex amalgamations at each hierarchical level leading to the complex distribution of shale drapes. Due to limitation of data, to build models realistically honoring the reservoir architecture provides an effective way to reduce risk and improve hydrocarbon rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…It is important to classify the deep‐marine deposition into channel, proximal lobe, medial lobe, and distal lobe settings (Figure 12a) (Kane et al, 2017; L.‐F. Zhang et al, 2020). The proximal lobes comprised of more thickness of sandstones than the distal ones, because more sediments are available in the vicinity of feeder channel in the proximal lobe settings (Fildani et al, 2018; L.‐F.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to classify the deep‐marine deposition into channel, proximal lobe, medial lobe, and distal lobe settings (Figure 12a) (Kane et al, 2017; L.‐F. Zhang et al, 2020). The proximal lobes comprised of more thickness of sandstones than the distal ones, because more sediments are available in the vicinity of feeder channel in the proximal lobe settings (Fildani et al, 2018; L.‐F.…”
Section: Discussionmentioning
confidence: 99%
“…Deep TEN (Zhang et al, 2020) is a Convolutional Neural Network (CNN) model architecture that adapts dictionary learning, a popular and successful approach to image texture classification (Liu et al, 2019), as a trainable component of the neural network. We adapted the network to take depth-aligned core images as input (see Figure 5), and predict sequences of labels as output (rather than a single classification per image) (Figure 7).…”
Section: Deep Ten For Use With Image Datamentioning
confidence: 99%
“…One way to extend the prediction capability is by incorporating spatial information and metrics. For example, utilizing forward stratigraphic models to generate stratal surfaces, geometries, and scales could be incorporated into spatial prediction of lithology and facies (Mulder et al, 1997;Tinterri et al, 2003;Pyrcz et al, 2005;McHargue et al, 2011;Albertão and Athayde, 2015;Burgess et al, 2019;Zhang et al, 2020). The model results might also provide another metric to score the results from machine-learning outputs.…”
Section: Comparison With Other Modeling Workflowsmentioning
confidence: 99%
“…Furthermore, past sedimentological studies of turbidite deposits, in ancient records and in modern environments, have called into question the previously established criteria for turbidites (Shanmugam, 1997(Shanmugam, , 2016. These studies have proposed new conceptual models (Lowe, 1982;Haughton et al, 2009;Stow & Smillie, 2020;Zhang et al, 2020) and highlighted the significance of interaction or alternation in sedimentary processes (Mutti, 2011;de Castro et al, 2020. Mulder et al (2008) suggested that interactions between turbidity and bottom currents can generate three distinct types of deposits: (i) alternations of turbidites and contourites (Stow et al, 1998;Michels et al, 2002;Brackenridge et al, 2013); (ii) redistributed or reworked gravity-driven deposits (Mutti, 1992;Stow et al, 2002;Hanquiez et al, 2010;Gong et al, 2013); and (iii) synchronous (mixed or hybrid) deposits (Sansom, 2018;Fonnesu et al, 2020;Fuhrmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, past sedimentological studies of turbidite deposits, in ancient records and in modern environments, have called into question the previously established criteria for turbidites (Shanmugam, 1997, 2016). These studies have proposed new conceptual models (Lowe, 1982; Haughton et al ., 2009; Stow & Smillie, 2020; Zhang et al ., 2020) and highlighted the significance of interaction or alternation in sedimentary processes (Mutti, 2011; de Castro et al ., 2020, 2021). Mulder et al .…”
Section: Introductionmentioning
confidence: 99%